Clinical Profile of Invasive Pneumococcal Disease in Patan Hospital, Nepal - Chhetri, U D; Shrestha, S; Pradhan, R; Shrestha, A; Adhikari, N; Thorson, S; Pollard, A J; Murdoch, D R; Kelly, D F (Kathmandu University Medical Journal, 2012)
Background Pneumococcal infection is one of the leading causes of pneumonia, meningitis and septicemia in developing countries. It accounts for one million deaths each year in children. Objectives The objective of this study is to see the clinical profile of invasive pneumococcal disease, antibiotics sensitivity pattern and prevalent serotypes in children admitted at Patan Hospital. Methods This is a retrospective analytical study conducted in the department of Paediatrics, Patan hospital. The lab data of those children who grew pneumococci in their blood, cerebrospinal fluid or body fluids over a period of 3 years (January 2007 to Dec 2009) were collected and the case files were then studied. Results Out of 42 cases of invasive pneumococcal diseases studied admitted diagnoses included pneumonia, febrile seizure, bacteremia or septicemia, meningitis, acute gastroenteritis and glomerulonephritis. Twenty seven of them were children under five. The male to female ratio was 1.7:1. On investigation 64%, 52% and 5% of the patients had leucocytosis, anaemia, and leucopenia respectively. Twenty six of them had radiological changes suggestive of pneumonia. Streptococcus pneumoniae grew in 38 blood samples, 5 cerebrospinal fluid and 3 pleural fluids. Almost all of these isolates were sensitive to penicillin, cefotaxime, amoxycillin, choloramphenicol, erythromycin and ofloxacin and resistant to cotrimoxazole and gentamicin.Pneumococcal serotypes found in our study were 1, 14, 5, 23B, 6B, 8, 9A, 9V, 10A, 15 and 23F (11 serotypes). Conclusions Penicillin is still the most effective antibiotic for streptococcal infection in our study. Of the pneumococcal serotypes identified; 36% were covered by the 7-valent pneumococcal conjugate vaccine, 54% each by PCV-10 and PCV-13, and 72% by the e 23 valent vaccines. http://dx.doi.org/10.3126/kumj.v9i1.6262 Kathmandu Univ Med J 2011;9(1):45-9